(3GdchGcH GdSGFQI HCYjGf GdeGFI GdYGTQIs - (3fLe GdOjf GdZRj , eMeO Hf eMeO Hf eMeO GdZRj GdYGeQj GdbQTj, fLe GdOjf CHh GdecGQe,J (B1061 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYdeGA fLhekG s
(3QJH GdWHbGJ Ydi MQha GdeYLes
(3cJHJ HQSe NRGfI GdSjO Ydi GdeQGOi eaJi GdMfajIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B288s
Keywords: (3GdJGQjNs